Utilization of bauxite waste as a fine aggregate material for concrete roads: A critical review - Alamsyah A. M.; Pratikso; Mudiyono R.; Wahyudi Biantoro A. (BIO Web of Conferences)
Bauxite tailings are an abundant waste product with no economic value. This research uses a critical review to describe the potential of bauxite tailings as a substitute for fine aggregate in concrete mixtures for road construction. There are differences in the Composition of the bauxite tailings used in the concrete mix, which will influence the results of testing the compressive strength and elasticity of the resulting concrete. This result used 30% and 70% bauxite tailings composition to replace fine aggregate in the concrete mix. Various studies on red mud substitute concrete show differences in mechanical properties and durability compared to Ordinary Portland Cement (OPC) concrete. Using up to 20% red mud by weight of cement improves adhesion and pressure quality in mortar compared to ordinary cement mortar. However, replacing more than 20% of cement with red mud reduces concrete’s compressive strength and stiffness, and more than 15% substitution lowers stress and bond-breaking quality. Thus, the analysis results show a tendency to use red mud as a cement substitute in concrete, with the best compressive strength and solid mass stiffness of concrete in the range of 15 – 20%.